2021
DOI: 10.1029/2019rg000683
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Drought: Definition, Challenges, and Opportunities

Abstract: Traditional, mainstream definitions of drought describe it as deficit in water-related variables or water-dependent activities (e.g., precipitation, soil moisture, surface and groundwater storage, and irrigation) due to natural variabilities that are out of the control of local decision-makers. Here, we argue that within coupled human-water systems, drought must be defined and understood as a process as opposed to a product to help better frame and describe the complex and interrelated dynamics of both natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 203 publications
(108 citation statements)
references
References 288 publications
(424 reference statements)
1
106
0
1
Order By: Relevance
“…Iran has been under a prolonged drying condition since the early twenty-first century, revealing itself by vanishing lakes and wetlands 40 along with excessive water stress across the country 25 . As it was previously shown for the case of surface water availability in Iran 33 , such drought conditions are human-induced and are exemplifiers of "anthropogenic droughts" 41,42 , which refer to water stress caused or intensified by aggressive, short-sighted and unsustainable land and water management 25,[41][42][43] . Here, the condition of anthropogenic drought is manifested by excessive ratios of water withdrawal to available renewable groundwater resources across Iran's major basins.…”
Section: Discussionmentioning
confidence: 94%
“…Iran has been under a prolonged drying condition since the early twenty-first century, revealing itself by vanishing lakes and wetlands 40 along with excessive water stress across the country 25 . As it was previously shown for the case of surface water availability in Iran 33 , such drought conditions are human-induced and are exemplifiers of "anthropogenic droughts" 41,42 , which refer to water stress caused or intensified by aggressive, short-sighted and unsustainable land and water management 25,[41][42][43] . Here, the condition of anthropogenic drought is manifested by excessive ratios of water withdrawal to available renewable groundwater resources across Iran's major basins.…”
Section: Discussionmentioning
confidence: 94%
“…These two questions will be addressed from a meteorological point of view by looking at the impact of climate change on the precipitation deficit. We realize that this is only the first step in analyzing the drivers of a complex phenomenon like a drought, which is not only caused by large scale circulation anomalies but also by complex interactions of local precipitation, wind, temperature, land use, and water management (Mishra and Singh 2010;AghaKouchak et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent decades have seen large collaborative efforts to produce downscaled climate datasets to provide information regarding current and future climate. The need for this information is crucial as many studies have suggested changes in the global hydrological cycle in response to global warming, leading to global and regional scale changes in: drought risk and severity (Diffenbaugh et al 2015;Apurv et al 2019;Marvel et al 2019;Alizadeh et al 2020;AghaKouchak et al 2021) on one hand, and more intense and more frequent rainfall on the other (Marvel and Bonfils 2013;Westra et al 2013;Fischer and Knutti 2015;Prein et al 2017;Reidmiller et al 2018;Myhre et al 2019). At the wet end, extreme rainfall events have the potential for producing devastating effects, such as flooding, damage to public infrastructure (e.g., dams, highways etc.…”
Section: Introductionmentioning
confidence: 99%